2018
DOI: 10.1155/2018/4049212
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Barriers to Antepartum HIV Medication Adherence in HIV Infected Pregnant Women

Abstract: Introduction Although rare, perinatal HIV transmission still occurs in the United States and most transmissions are preventable. We aim to identify patient barriers to antiretroviral therapy (ART) adherence during pregnancy and assess patient understanding of perinatal transmission. Methods This cross-sectional survey recruited HIV positive postpartum women at a large safety net hospital in Atlanta, Georgia, between January 2016 and February 2018. Survey questions included demographic characteristics, HIV hist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 10 publications
(13 reference statements)
0
2
1
Order By: Relevance
“…Consistent with our results, high HIV prevalence was reported in pregnant women from urbanized areas in the Democratic Republic of the Congo, 20 and Tanzania, 13 but different results were reported in Rwanda, 19 Cameroon, 17 and Ethiopia. 21 In contrast with our results, low HIV prevalence was observed in pregnant women with a high educational level in the USA, 22 and China. 23 The high prevalence of HIV/HBV co-infection observed is not surprising since the HIV/HBV co-infection in sub-Saharan Africa is estimated at 6% to 25%.…”
Section: Discussioncontrasting
confidence: 99%
“…Consistent with our results, high HIV prevalence was reported in pregnant women from urbanized areas in the Democratic Republic of the Congo, 20 and Tanzania, 13 but different results were reported in Rwanda, 19 Cameroon, 17 and Ethiopia. 21 In contrast with our results, low HIV prevalence was observed in pregnant women with a high educational level in the USA, 22 and China. 23 The high prevalence of HIV/HBV co-infection observed is not surprising since the HIV/HBV co-infection in sub-Saharan Africa is estimated at 6% to 25%.…”
Section: Discussioncontrasting
confidence: 99%
“…This therefore means that despite disparities in the level of education there is an association between level of education and ART adherence. These findings confirm that lack of knowledge regarding perinatal transmission is the major hindrance to ART adherence [8]. This knowledge gap can be closed if we continue giving health messages during perinatal visits as was explained by health care workers during the interview.…”
Section: Yes Nosupporting
confidence: 75%
“…Three articles revealed that lack of confidence in ART efficacy promoted non adherence to the therapy 23,24,28 . Some women believed that ART was harmful to themselves and their unborn babies 28 and some women discontinued the therapy after experiencing ART adverse effects, leading to doubts in the efficacy of the treatment 23 .…”
Section: Resultsmentioning
confidence: 99%
“…Three articles revealed that lack of confidence in ART efficacy promoted non adherence to the therapy 23,24,28 . Some women believed that ART was harmful to themselves and their unborn babies 28 and some women discontinued the therapy after experiencing ART adverse effects, leading to doubts in the efficacy of the treatment 23 . In a different study, it was observed that although the women accepted ART, members of the community demonstrated a lack of information about its benefits and consequently discriminated against those who took up the therapy 21 …”
Section: Resultsmentioning
confidence: 99%